Performance-based payment structural design for infrastructure PPP projects - Su, Limin; Cao, Yongchao; Li, Huimin (International Journal of Strategic Property Management, 2023)
The performance-based payment structure has been widely used in infrastructure PPP projects. However, existing research has been absent on the structural unbalance problem of performance-based payment in the current infrastructure PPP projects. This study aims to construct an optimal proportion of the performance-based payment in the total payment, and then design a performance-based payment structure for infrastructure PPP projects. Firstly, the definition of the performance-linked rate is introduced to characterize the proportion of the performance-based payment. Secondly, based on the different objectives of the maximum social benefit and the minimum cost for the public and private sectors, a multi-objective optimization model is constructed to obtain a reasonable value range of the performance-linked rate. Thirdly, the impacts on different parameters in the performance-linked rate are revealed using simulation methods. Finally, the numerical and simulation results show that, for the weak social average ability, the social cost is also high, and a large performance-linked rate should be set. Conversely, when the social average ability is strong, the social average cost is relatively reduced, and a relatively low performance-linked rate should be set. Consequently, the results can guide the contract design in PPP projects.